Study on UAV Based on Fused Filament Fabrication - Li Zheng Yu (International Journal of Engineering Continuity, 2022)
Air Unmanned Aerial Vehicles (UAVs) have the characteristics of simple structure and convenient carrying, while quadrotor UAVs have better manoeuvrability, can achieve fixed-point hover, and have vertical takeoff and landing capabilities. Additive Manufacturing (AM) is also often referred to as 3D printing. In the past ten years, AM technology has received extensive attention. Among the seven categories of AM technologies released by the American Society for Testing and Materials, Fused Filament Fabrication (FFF) is one of the most widely used and essential processing technologies in additive manufacturing. It mainly manufactures models by extruding molten wire (such as plastics, resins, composites, etc.). First, consider the additive manufacturing of the quadrotor aerial UAV entirely through fused filament fabrication, and control the UAV's flexibility by adjusting the filling material's parameter during the additive manufacturing process. However, the increased flexibility makes it difficult to control the UAV, and the structural, aerodynamic and aeroelastic effects must be further explored.